Simultaneous early-onset immune thrombocytopenia and autoimmune thyroid disease following alemtuzumab treatment in relapsing-remitting multiple sclerosis. (August 2016) - Obermann, Mark; Ruck, Tobias; Pfeuffer, Steffen; Baum, Julia; Wiendl, Heinz; Meuth, Sven G
Objective: We report two cases of patients with relapsing-remitting multiple sclerosis with early-onset thrombocytopenia and autoimmune thyroid disease after the first treatment course with 60-mg alemtuzumab. Methods: Case series and review of the literature. Results: Both patients showed severe thrombocytopenia with platelet counts of 2 × 10 9 and 11 × 10 9 /L, respectively, as well as increased thyroid antibodies within only a few months after initiating alemtuzumab treatment (11 and 9 months). Both patients responded considerably well to medical therapy including corticosteroids and intravenous immunoglobulins with slow platelet recovery over several weeks. Interestingly, both patients were previously treated with fingolimod and showed a marked lymphocytopenia that led to discontinuation. Conclusion: These cases emphasize the necessity of careful clinical surveillance and proper education of patients treated with alemtuzumab as proposed by the safety-monitoring program. Previous severe lymphocytopenia under therapy with other disease-modifying therapies may be a risk factor for the development of immune thrombocytopenia.